Integrated care at the emergency department: an investment for better health - Steven Hoon Chin Lim; Colin Eng Choon Ong; Arron Seng Hock Ang; Khai Pin Lee; Jean Mui Hua Lee; Venkataraman Anantharaman (Singapore Medical Journal)
It is crucial that policy makers, healthcare providers and relevant stakeholders understand how integrated care may be improved at our emergency departments (EDs) and what benefits that would bring. The potential that exists for right-siting care of special patient groups who could be managed in an ambulatory setting with the integration of a variety of hospital-based and community-based clinical support services is tremendous. This review describes the best practice and value of integrated care at the EDs. Local evidence is cited and compared with findings from overseas. The opportunities of care transition interventions among discharged patients are outlined, including that for paediatric patients, palliative care patients and patients with chronic diseases. This review also suggests ways to move forward to meet the aim of providing holistic care at EDs through integrated care programmes, innovation and research.